In silico improvement of the cyanobacterial lectin microvirin and mannose interaction. Issue 3 (2nd February 2022) - Lima, Adonis de Melo; Siqueira, Andrei Santos; Möller, Marina Luiza Saraiva; Souza, Rafael Conceição de; Cruz, Jorddy Neves; Lima, Alex Ranieri Jerônimo; Silva, Ronaldo Correia da; Aguiar, Délia Cristina Figueira; Junior, João Lídio da Silva Gonçalves Vianez; Gonçalves, Evonnildo Costa
Abstract: Lectins that bind to HIV envelope glycoprotein can inhibit virus-cell fusion and be used for rational drug design. This paper presents the results of an in silico approach to improve affinity interaction between the cyanobacterial lectin microvirin and its ligand Manα(1-2)Man. Comparative modeling and molecular dynamics tools were used. Additionally, the alanine scanning webserver was used to study the importance of protein residues in the binding site and to guide mutant production. The model obtained presented two homologous domains designated as domains A and B, each consisting of a single strand with triple and antiparallel β-sheets of (β1-β3 and β6-β8). Disulfide bonds between the cysteines (Cys60-Cys80, Cys63-Cys78 and Cys8-Cys24) were also found. The highly conserved binding site, including residues Asn44, Ile45, Asp46, Gln54, Asn55, Glu58, Thr59, Gln81, Thr82 and Met83. The RMSD values of the di-mannose and the interaction site were very stable during the molecular dynamics. Calculations of the occupation time of the hydrogen bonds were made for the residues that showed interaction in the complex lectin and ligand. The residue that contributed most to the interaction with Manα(1-2)Man was Asn55. After validation, the model generated remained stable during the entire simulation. Despite its structural similarity with the template we used, our mutant (Thr82Arg) showed a higher affinity interaction with Manα(1-2)Man. Communicated by Ramaswamy H. Sarma